2016
DOI: 10.5527/wjn.v5.i1.76
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium in polycystic kidney disease: From signaling to pathology

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited monogenic kidney disease. Characterized by the development and growth of cysts that cause progressive kidney enlargement, it ultimately leads to end-stage renal disease. Approximately 85% of ADPKD cases are caused by mutations in the PKD1 gene, while mutations in the PKD2 gene account for the remaining 15% of cases. The PKD1 gene encodes for polycystin-1 (PC1), a large multi-functional membrane receptor protein able to regulate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
(67 reference statements)
1
24
0
1
Order By: Relevance
“…Misregulation of Ca 2ϩ -dependent signal transduction is associated with cyst formation (27,30). To determine whether VX-809 alters Ca 2ϩ movement, we treated the cells with ATP, which stimulates purinergic receptors (31) and found ( Fig.…”
Section: Vx-809 Down-regulates Resting Intracellular Ca 2؉ Levels Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Misregulation of Ca 2ϩ -dependent signal transduction is associated with cyst formation (27,30). To determine whether VX-809 alters Ca 2ϩ movement, we treated the cells with ATP, which stimulates purinergic receptors (31) and found ( Fig.…”
Section: Vx-809 Down-regulates Resting Intracellular Ca 2؉ Levels Andmentioning
confidence: 99%
“…Misregulation of Ca 2ϩ is associated with cyst formation in ADPKD (35), with some investigators reporting that disruption of Ca 2ϩ signaling is the primary event that supports increased cyst growth (30). Several studies have shown that a reduction in the function of either PC1 or PC2 leads to dysregulation of Ca 2ϩ signaling (see Ref.…”
Section: Vx-809 Reduces Ca 2؉ Movement Out Of the Ermentioning
confidence: 99%
“…Misregulation of Ca 2+ is associated with cyst formation in ADPKD[13], with some investigators reporting that disruption of Ca 2+ signaling is the primary event that supports increased cyst growth[14]. Several studies have shown that a reduction in the function of either PC1 or PC2 leads to dysregulation of Ca 2+ signaling (see [9] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…The null cells (PN) stably express the Cre recombinase, and the control cells (PH) are from the original clone, which is heterozygous for the expression of PC1 [18, 19]. Others have shown that expression of the C-terminal fragment of PC1 can cause an increase in basal levels of intracellular Ca 2+ and induce abnormal Ca 2+ oscillations, which also result in increases in cell signaling [14]. Thus, there appears to be a dichotomy of thought on how Ca 2+ plays a role in ADPKD with some thinking that Ca 2+ restriction causes cyst growth and others that enhanced release of Ca 2+ from the ER is the major factor which fuels cyst growth.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время широко обсуждаются вопросы лечения наследственных заболеваний [1,2]. Лечение, воздействующее на основные патогенетические звенья роста кист при поликистозе почек, направлено: 1) на уменьшение пролиферации эпителиальных клеток канальцев и секреции жидкости за счет снижения уровня внутриклеточного Ca 2+ ; 2) на подавление эпидермального фактора роста (EGFR), уменьшение уровня цАМФ и снижение активности cSrc (тирозинкиназы, принимающей участие в процессе клеточного роста; cSrc является посредником в перекрестной связи EGFR и G-белка цАМФ) [7,23,24]. Кроме того, обсуждается поиск путей воздействия на восстановление клеточно-клеточных и клеточно-матриксных связей, угнетение прогрессирующего интерстициального фиброза, связанного с повреждением макрофагов, и подавление пути mTOR (mammalian target of rapamycin -мишени рапамицина млекопитающих) [23,25].…”
unclassified